2012
DOI: 10.1111/j.1365-2265.2011.04209.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural evaluation of hearing in acromegaly

Abstract: Summary Context  The impact of acromegaly on the auditory system remains unknown. Objective  This study aimed to examine audiological symptoms and the structure and function of the auditory system in patients with acromegaly. Design/Setting and Patients  The study included 44 patients with acromegaly. Pure tone audiometry, speech audiometry, tympanometry, otoacoustic emissions testing, computerized tomography of the temporal bone and magnetic resonance imaging of the ear were performed in all patients. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
4
1
1
Order By: Relevance
“…Aydin et al 14 found a HL prevalence of 48%; 30% sensorineural; however, they used PTA > 15 DBHL as criterion, more sensitive than what was used in the present study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Aydin et al 14 found a HL prevalence of 48%; 30% sensorineural; however, they used PTA > 15 DBHL as criterion, more sensitive than what was used in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Aydin et al 14 published recently the results from functional and structural assessment of hearing in a group of 44 patients. Besides the audiometry and impedance measures, they also carried out MRI of the ear.…”
Section: Introductionmentioning
confidence: 99%
“…Aydin et al (2012) 6 conducted a study to profile the audiological and structural function in patients with acromegaly. The evaluated group was composed of 44 patients with acromegaly and 36 healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Graham and Brackmann observed hypertrophy of the mastoid cortical bone and posterior bony wall in three patients with acromegaly during middle ear surgery. 6 …”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, hearing loss may be caused by middle ear pressure dysregulation, sclerosis of mastoid, recurrent otitis, plaque formation, and GH excess associated increase in perilymph formation. [3]…”
Section: Hearing and Hypothalamic-pituitary Disordersmentioning
confidence: 99%